AUTHORITARIAN PRESS. IN THE ROLE OF INFORMATION AND PSYCHOLOGICAL INFLUENCE (American Journal of Business Management, Economics and Banking, 2024)
Due to the need for social information exchange, the period when the first forms of mass media, including leaflets and newspapers, began to appear, shows that most of the press publications were published by the rulers and served their interests. "These press releases were created as a result of the socio-political interests of the rulers of that time together with the need of people for information. World press studies call such a press that supports the rule of individuals as an authoritarian press," writes Professor M. Khudoykulov, doctor of philological sciences.